2017
DOI: 10.1371/journal.pone.0185802
|View full text |Cite
|
Sign up to set email alerts
|

Rejection sensitivity as a vulnerability marker for depressive symptom deterioration in men

Abstract: Consistent across time and cultures, men and male adolescents older than 14 years of age appear underrepresented in mood disorders, and are far less likely than women to seek psychological help. The much higher rate of suicide amongst males suggests that depression in men might be underreported. One of the core human motives is to seek acceptance by others and avoid rejection. Rejection Sensitivity (RS) has been conceptualized as the cognitive-affective processing disposition to anxiously expect, readily perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…However, the positive association between RS and depressive symptoms may be in part attributed to the overlap of the same underlying symptoms. Recent research demonstrates that high levels of RS are associated with depression (23)(24)(25). For instance, Chango et al (25) found that high RS in mid-adolescence could predict depressive symptoms in later adolescence.…”
Section: High Rejection Sensitivity In Patients With Somatoform Pain mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the positive association between RS and depressive symptoms may be in part attributed to the overlap of the same underlying symptoms. Recent research demonstrates that high levels of RS are associated with depression (23)(24)(25). For instance, Chango et al (25) found that high RS in mid-adolescence could predict depressive symptoms in later adolescence.…”
Section: High Rejection Sensitivity In Patients With Somatoform Pain mentioning
confidence: 99%
“…One recent review ( 22 ) also displays disturbances in RS across different personality disorders. Numerous studies have identified high levels of RS and hypervigilance for signs of rejection as predictors for depression ( 23 25 ). Results of a previous meta-analysis provide evidence for the association between RS and mental disorders, such as depression, anxiety, borderline personality disorder and eating and bodydysmorphic disorder ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, on the contrary, some researchers believed that ostracism would elicit emotional reactions but not cause distress nor depression [ 21 ]. The determinant for depression was rejection sensitivity or how individuals remembered the experience of ostracism [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, individuals with high rejection sensitivity pay attention to potential rejection cues in a biased manner (61), have schema-congruent information processing biases (62), experience much more rumination (63), and have interpretation biases (64). Consequently, through the distortion effect of rejection sensitivity, people with a high level of social stress experience more depressive symptoms than do those with a low level of social stress (32,65,66).…”
Section: Discussionmentioning
confidence: 99%